2023
DOI: 10.3390/su15065121
|View full text |Cite
|
Sign up to set email alerts
|

Digital Economy and the Sustainable Development of China’s Manufacturing Industry: From the Perspective of Industry Performance and Green Development

Abstract: Digital transformation is increasingly crucial to the upgrading and sustainable development of China’s manufacturing industry with the rapid development of the digital economy. To study the impact of the digital economy on the sustainable development of the manufacturing industry, this study analyzed the theoretical basis of the digital economy’s impact on the promotion of the sustainable development of the manufacturing industry. Then, based on the panel data of manufacturing sectors in 2002, 2005, 2007, 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In addition, with the improvement of industrial infrastructure, the DE is continuously increasing (Guanghao et al, 2022). The DE can increase industrial performance by reducing production costs (Kangxian et al, 2023), driving changes in production and lifestyle, reducing pollution emissions, and subsequently strengthening the capacity for sustainable "ecological-economic-social" development (Pradhan et al, 2020), promoting the green development of industry .…”
Section: The Digital Economy Green Transformation and Upgradingmentioning
confidence: 99%
“…In addition, with the improvement of industrial infrastructure, the DE is continuously increasing (Guanghao et al, 2022). The DE can increase industrial performance by reducing production costs (Kangxian et al, 2023), driving changes in production and lifestyle, reducing pollution emissions, and subsequently strengthening the capacity for sustainable "ecological-economic-social" development (Pradhan et al, 2020), promoting the green development of industry .…”
Section: The Digital Economy Green Transformation and Upgradingmentioning
confidence: 99%
“…Zhao et al (2022) empirically tested the positive impact of digital economy development on improving carbon productivity based on panel data from 285 prefecture level cities in China, using a bidirectional fixed effects model, an intermediary mechanism model, and a threshold mechanism model [40]. Ji et al (2023) pointed out that digital service has a significant positive impact on improving the performance level of MI and reducing the production cost of enterprises, and as an intermediate variable, it can effectively improve the innovation level of manufacturing enterprises to reduce carbon emissions and ultimately promote the digital green and sustainable development of enterprises [41]. Gao et al (2023) carried out analysis and research from the perspective of government support and stakeholders, and found that government subsidies, as an intermediary, affect the digitization level of enterprises and thus affect the GI of enterprises, and the fulfillment of corporate social responsibility also has a positive impact on GI [42].…”
Section: Factors Related To Dgi Performancementioning
confidence: 99%
“…In recent years, some scholars have begun to conduct some exploratory studies on the role of the digital economy in promoting the transformation and upgrading of the manufacturing industry. Some scholars discussed the driving role of the digital economy in the green development of the manufacturing industry from the perspectives of industry performance [20], geographical agglomeration [21], and global value chain [22]. Cai Yanze et al (2021) and Yu Donghua and Wang Meijuan (2022), respectively, introduced factors such as innovation environment and entrepreneurship to analyze the mechanism of the digital economy on manufacturing upgrading [23,24].…”
Section: Literature Reviewmentioning
confidence: 99%